QARAQALPAQSTAN FLORASÍNDA TARQALǴAN EFIR MAYLÍ ÓSIMLIKLER - Temirbekov, O. (ILIM hám JÁMIYET, 2025)
The article presents the total number of species of essential vólatile oil plants growing in the flora of the Republic of Karakalpakstan, as well as their distribution in botanical and geographical areas.